Perception of Postgraduate Students on the Integration of Social Media in Learning in South-West, Nigeria - Odewumi, Michael Olubunmi (Journal of Education and Research, 2019)
Social media is a technology, which came into existence out of curiosity for social interaction to connect people but has evolved to become an influential tool for teaching and learning globally. However, despite its usefulness and relevance to learning, the perception, Ease of Use (EoU), Perceived Usefulness (PU), Self-efficacy (Se), and intention to integrate social media into learning by postgraduate students have not been substantially established. Therefore the objectives of this study were to: (i) identify the social media used by postgraduate students; (ii) investigate postgraduate students’ PU, EoU, Se and intention to use social media for learning; (iii) investigate the relationships among postgraduate students’ PU, EoU, Se, and the intention to use social media for learning; (iv) examine the influence of postgraduate students’ gender on their PU, EoU, Se, and intention to use social media for learning; and (v) determine the influence of postgraduate students’ discipline on their PU, EoU, Se, and the intention to use social media for learning.